Biocomposites from Colombian Sugarcane Bagassewith Polypropylene: Mechanical, Thermal and Viscoelastic Properties (2018)
Biocomposites are materials formed by mixing a polymer matrix and a filler or reinforcement, with the characteristic that at least one should be of biological origin. For this study, biocomposites were obtained from natural fibers of cane bagasse and polypropylene, using bagasse from postindustrial sources, originating from the production of sugarcane from the Valle-Cauca region in Colombia. In addition, cane bagasse fibers were treated chemically, with the purpose of improving the interfacial relationship. Polypropylene homopolymer was used as a polymeric matrix, which was mixed in a twin screw extruder, obtaining different materials as biocomposites. Finally, it was possible to obtain a suitable biocomposite for application in injection molding processes and studying its mechanical, viscoelastic, and thermal behaviors, through DSC, TGA, DMA, and SEM techniques